Clofarabine, high-dose cytarabine and liposomal daunorubicin in pediatric relapsed/refractory acute myeloid leukemia: a phase IB study - van Eijkelenburg, Natasha K A; Rasche, Mareike; Ghazaly, Essam; Dworzak, Michael N; Klingebiel, Thomas; Rossig, Claudia; Leverger, Guy; Stary, Jan; De Bont, Eveline S J M; Chitu, Dana A; Bertrand, Yves; Brethon, Benoit; et al. (Haematologica, 2018)
Survival in children with relapsed/refractory acute myeloid leukemia is unsatisfactory. Treatment consists of one course of fludarabine, cytarabine and liposomal daunorubicin, followed by fludarabine and cytarabine and stem-cell transplantation. Study ITCC 020/I-BFM 2009-02 aimed to identify the recommended phase II dose of clofarabine replacing fludarabine in the abovementioned combination regimen (3+3 design). Escalating dose levels of clofarabine (20-40 mg/m2/day × 5 days) and liposomal daunorubicin (40-80 mg/m2/day) were administered with cytarabine (2 g/m2/day × 5 days). Liposomal DNR was given on day 1, 3 and 5 only. The cohort at the recommended phase II dose was expanded to make a preliminary assessment of anti-leukemic activity. Thirty-four children were enrolled: refractory 1st (n=11), early 1st (n=15), ≥2nd relapse (n=8). Dose level 3 (30 mg/m2clofarabine; 60 mg/m2liposomal daunorubicin) appeared to be safe only in patients without subclinical fungal infections. Infectious complications were dose-limiting. The recommended phase II dose was 40 mg/m2 clofarabine with 60 mg/m2 liposomal daunorubicin. Side-effects mainly consisted of infections. The overall response rate was 68% in 31 response evaluable patients, and 80% at the recommended phase II dose (n=10); 22 patients proceeded to stem cell transplantation. The 2-year probability of event-free survival (pEFS) was 26.5±7.6 and probability of survival (pOS) 32.4±8.0%. In the 21 responding patients, the 2-year pEFS was 42.9±10.8 and pOS 47.6±10.9%. Clofarabine exposure in plasma was not significantly different from that in single-agent studies. In conclusion, clofarabine was well tolerated and showed high response rates in relapsed/refractory pediatric acute myeloid leukemia. Patients with (sub) clinical fungal infections should be treated with caution. Clofarabine has been taken forward in the Berlin-Frankfurt-Münster study for newly diagnosed acute myeloid leukemia. The Study ITCC-020 was registered as EUDRA-CT 2009-009457-13; Dutch Trial Registry number 1880.
Keywords: Antineoplastic Combined Chemotherapy Protocols; cytarabin; ženské pohlaví; mladiství; Clofarabine; klofarabin; lidé; Liposomes; recidiva; protokoly protinádorové kombinované chemoterapie; Drug Administration Schedule; Survival Analysis; mladý dospělý; Cytarabine; Child; předškolní dítě; daunomycin; liposomy; Child, Preschool; chemorezistence; Humans; Retreatment; výsledek terapie; Infant; mužské pohlaví; Daunorubicin; rozvrh dávkování léků; analýza přežití; opakovaná terapie; Male; Drug Resistance, Neoplasm; akutní myeloidní leukemie; kojenec; Young Adult; Remission Induction; Treatment Outcome; Adolescent; Leukemia, Myeloid, Acute; indukce remise; Recurrence; Female; dítě